Simple Capacitor Voltage Balancing for Three-Level NPC Inverter Using Discontinuous PWM Method with Hysteresis Neutral-Point Error Band - Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2021)
Three-level neutral-point-clamped (3L-NPC) voltage source inverters are widely used in many low- and medium-power applications. However, the 3L-NPC inverter has an inheritance issue of the neutral-point (NP) voltage unbalancing due to the deviation of dc-link capacitor voltages causing distortions for the output waveform quality. Generally, discontinuous pulsewidth modulation (DPWM) is used to diminish the stress on power transistors and prolong their lifespan, however; it is not capable of solving the issue of NP voltage unbalancing. Therefore, this article proposes a simple voltage balancing control based on DPWM with a hysteresis NP voltage band. The balancing control method is only activated once the capacitance voltage error exceeds the hysteresis band by generating a momentary offset on the opposite direction of the DPWM offset. In this way, both top and bottom capacitance voltages will converge within a predefined error band. Various hysteresis error bands are investigated by analyzing the power losses, total harmonic distortions, and common mode voltage. The advantages of this proposed method are its simplicity and ease of control while maintaining the features of DPWM. The effectiveness of the proposed method is validated using simulation and experimental results.
Keywords: Capacitor voltage balancing; Dc-link capacitor voltages; Discontinuous pulse width modulations (DPWM); Three level NPC inverter; Three-level neutral point clamped; Total harmonic distortion (THD); Voltage balancing control; Voltage source inverter; Discontinuous pulsewidth modulation (DPWM); hysteresis neutral-point (NP) error band; NP voltage balancing; three-level NP clamped inverter (3L-NPC)